Aquaman and the lost kingdom [videorecording (Blu-Ray)] - Wan, James, 1977-; Johnson, David Leslie; Momoa, Jason; Momoa, Jason; Sibbett, Thomas Pa'a; Wilson, Patrick, 1973-; Heard, Amber, 1986-; Abdul-Mateen, Yahya, II, 1986-; Park, Randall; Lundgren, Dolph, 1959-; Morrison, Temuera; Short, Martin, 1950-; et al. (Warner Bros. Entertainment Inc., 2024)
After failing to defeat Aquaman the first time, Black Manta wields the power of the mythic Black Trident to unleash an ancient and malevolent force. Hoping to end his reign of terror, Aquaman forges an unlikely alliance with his brother, Orm, the former king of Atlantis. Setting aside their differences, they join forces to protect their kingdom and save the world from irreversible destruction.